Psychological Aspects of Women Facing Infertility: Aspek Psikologis Wanita yang Menghadapi Infertilitas - Annisak, Aviatul; Azizah, Nurul (Inquest Journal, 2024)
This study examines the psychological impact of infertility on Mrs. V, a 24-year-old woman who has not conceived after two years of marriage. Infertility in women can significantly affect their psychological well-being, leading to anxiety and stress. This case study aims to describe Mrs. V's psychological condition, and the interventions used to alleviate her distress. Infertility midwifery care and a personal approach, combined with emotional support, were implemented as treatment methods. Results indicate that these interventions helped reduce Mrs. V's anxiety, emphasizing the importance of emotional support and assistance from her husband. The findings suggest that comprehensive care and strong spousal support are crucial in managing the psychological effects of infertility in women.